The long walk - Zwicky, Jan, 1955- (Oskana poetry & poetics., 2016)
"In The Long Walk, Jan Zwicky bears witness to environmental and cultural cataclysm. Both prophetic and acutely personal, these poems extend her previous meditations on colonial barbarism and ecocide, on spiritual catastrophe and transformation. The voice now penetrates the steepest darknesses; it possesses extraordinary reach and density. Zwicky is one of North America's finest poets, and in this book, she gives us her most profound work to date."--